MOTIVASI DIBALIK PENINGKATAN OFFICIAL DEVELOPMENT ASSISTANCE JEPANG KE KAWASAN AFRIKA TAHUN 2008-2019 - Rachmat Afi Azzam Pehang; Arie Kusuma Paksi (Jurnal Studi Diplomasi dan Keamanan, 2021)
This research analyses he motivation behind the improvement of Japanese Official Development Assistance (ODA) to African Region in 2008-2019. By using the qualitative research method, this researh analyzes various literatures related to the research investigated. Based on the data obtained the African Region have never been the Japan’s main focus of aid intervention. However, when it entered the era of the 2000s, and in 2008 it became an important moment, when the ODA distribution policy for African Region was increasingly getting the main focus compared to other regions. Using the theory of national interest, the presence of Japan through increasing the distribution of ODA in the African Region is based the calculation of the African Region economic benefits for Japan.